REE MINERALS IN BLACK SHALES OF THE PALEOPROTEROZOIC MIKHAILOVKA FORMATION (BAIKAL-PATOM HIGHLAND, SIBERIA) - E.E. Palenova; E.A. Rozhkova; E.V. Belogub; M.A. Rassomakhin (Минералогия)
The paper characterizes REE mineralization from carbonaceous metapelites of the Paleoproterozoic Mikhailovka Formation, which is the most ancient gold-bearing horizon of the Lena province (Bodaibo district, Irkutsk region). The conditions of metamorphism of the studied samples do not exceed those of chlorite-muscovite subfacies of greenschist facies (ilmenite-pyrrhotite isograde). The metamorphic allanite is a main REE host, which crystallized before the last stage of plastic deformation and folding. The matter source for its formation is related to REE and Th absorbed on organic matter and clay minerals, as well as the detrital monazite. Late hydrothermal-metasomatic processes resulted in its replacement by hydroxycarbonates (hydroxybastnaesite, ancylite) and hydrous phosphates of light REEs (rhabdophane?), while Th precipitated as a hydrous silicate. Findings of low-temperature metamorphic monazite and xenotime are also described.